The summer of Jordi Perez (and the best burger in Los Angeles) - Spalding, Amy (Sky Pony Press, 2018)
"Seventeen, fashion-obsessed, and gay, Abby Ives has always been content playing the sidekick in other people's lives. While her friends and sister have plunged headfirst into the world of dating and romances, Abby's been happy to focus on her plus-size style blog and her dreams of taking the fashion industry by storm. When she lands a great internship at her favorite boutique, she's thrilled to take the first step toward her dream career. Then she falls for her fellow intern, Jordi Perez. Hard. And now she's competing against the girl she's kissing to win the coveted paid job at the end of the internship. But really, nothing this summer is going as planned. She also unwittingly becomes friends with Jax, a lacrosse-playing bro-type who wants her help finding the best burger in Los Angeles, and she's struggling to prove to her mother--the city's celebrity health nut--that she's perfectly content with who she is. Just as Abby starts to feel like she's no longer the sidekick in her own life, Jordi's photography surprisingly puts her in the spotlight. Instead of feeling like she's landed a starring role, Abby feels betrayed. Can Abby find a way to reconcile her positive yet private sense of self with the image others have of her?"--Front flap.